2006
DOI: 10.1177/1362361306062021
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and attention abnormalities in autistic spectrum disorders

Abstract: Individuals with autistic spectrum disorders (ASDs) often experience, describe and exhibit unusual patterns of sensation and attention. These anomalies have been hypothesized to result from overarousal and consequent overfocused attention. Parents of individuals with ASD rated items in three domains, 'sensory overreactivity', 'sensory underreactivity' and 'sensory seeking behaviors', of an expanded version of the Sensory Profile, a 103-item rating scale developed for the present study. Parents also rated sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
333
4
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(384 citation statements)
references
References 32 publications
27
333
4
11
Order By: Relevance
“…Again, this relationship may link to the requirement to seek sensory stimulation that can regulate arousal. Repetitive behaviours have been proposed to regulate arousal in children with ASD (Gabriels, et al, 2008;Liss, et al, 2006). Research of the nature reported here questions the specificity of that relationship to ASD and considers the possible link between these phenomena across neuro-developmental disorders.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Again, this relationship may link to the requirement to seek sensory stimulation that can regulate arousal. Repetitive behaviours have been proposed to regulate arousal in children with ASD (Gabriels, et al, 2008;Liss, et al, 2006). Research of the nature reported here questions the specificity of that relationship to ASD and considers the possible link between these phenomena across neuro-developmental disorders.…”
Section: Methodsmentioning
confidence: 87%
“…Repetitive behaviours may be functional in regulating arousal levels for children with ASD who experience sensory processing abnormalities (e.g. Gabriels et al, 2008;Liss, Saulnier, Fein, & Kinsbourne, 2006). Furthermore, sensory seeking may be an intrinsic motivator for repetitive behaviours in children with ASD and those with intellectual disability (Joosten, Bundy & Einfeld , 2009).…”
Section: Exploring the Relationship Between Sensory Processing And Rementioning
confidence: 99%
“…Equally underlying weaknesses in attention have been shown to influence behavioural features of ID. For instance, the tendency to 'over focus' on particular stimuli in autism (Liss, Saulnier, Kinsbourne, & Kinsbourne, 2006;Patten & Watson, 2011), as well as the repetitive and stereotyped behaviours which are commonly reported in autism, are suggestive of impairments in inhibitory control (Richler, Huerta, Bishop, & Lord, 2010;Rodgers, Riby, Janes, Connolly, & McConachie, 2012). Equally the unique behavioural profile of individuals with WS which is characterized by a tendency to indiscriminately approach both familiar and unfamiliar individuals (Jones et al, 2000), has also been attributed to weaknesses in inhibitory control (Little et al, 2013;Porter, Coltheart, & Langdon, 2007).…”
Section: Attention Training Vs Working Memory Training In Intellectuamentioning
confidence: 99%
“…quiet or loud background noise) and social (e.g. an unexpected tap on the shoulder or a hug) sensory stimuli [Hilton, Graver, & LaVesser, 2007;Liss, Saulnier, Fein, & Kinsbourne, 2006], with the sensory stress acting as emotional triggers [Wood & Gadow, 2010].…”
Section: Modal Model Of Ermentioning
confidence: 99%